JAEPL, Vol. 21, Winter 2015-2016 - Joonna Smitherman Trapp; Brad Peters (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Essays Fond Farewells: Judy Halden-Sullivan and Helen Walker SPECIAL SECTION: RHETORIC AND ETHICS John M. Duffy - Reconsidering Virtue Lois Agnew - Why Rhetoric and Ethics? Revisiting History/Revising Pedagogy Paula Mathieu - Being There: Mindfulness as Ethical Classroom Practice Scott Wagar - Composition as a Spiritual Discipline Erec Smith - Buddhism’s Pedagogical Contribution to Mindfulness Peter H. Khost - “Alas, Not Yours to Have”: Problems with Audience in High-Stakes Writing Tests and the Promise of Felt Sense TEACHING AND LEARNING Sheri Rysdam & Lisa Johnson-Shull - Introducing Feedforward: Renaming and Reframing Our Repertoire for Written Response Mark Noe - Autoethnography and Assimilation: Composing Border Stories Irene A. Lietz - “When Do I Cross the Street?” Roberta’s Guilty Reflection Karen Lee Osborne - Toward a Poetics and Pedagogy of Sound: Students as Production Engineers in the Literature Classroom Out of the Box Robert M. Randolph - My Mom’s Letter Final Journals Book Reviews Julie Nichols - Reading Ethically Peter Fields - Gregory Marshall. Shaped by Stories: The Ethical Power of Narratives. Notre Dame, IN: U of Notre Dame P., 2009 Walter L. Reed - Gregory, Marshall. Teaching Excellence in Higher Education, ed. Melissa Valiska Gregory. NY: Palgrave Macmillan, 2013 Jeffrey H. Taylor - Musgrove, Laurence. Local Bird. Beaumont, TX: Lamar U Press, 2015 Warren Hatch - Lynch, Tom, Cheryll Glotfelty, Karla Armbruster. The Bioregional Imagination—Literature, Ecology, and Place. Athens, GA: U of GA Press, 2012 Connecting Helen Walker - More Apt, Connected Title Sheryl Lain - Hey, Teach! Do You Love Me? Matthew B. Ittig - Ask Me Tomorrow Laurence Musgrove - Writing Program Julie O’Connell - The Power of a Slave Narrative Leslie A. Werden - Embracing Chaos Donna Souder-Hodge - Teaching Dachau Tanya R. Cochran, Rasha Diab, Thomas Ferrel, & Beth Godbee - Hanging Out: Cultivating Life-Giving Writing Groups Online